Frontispiece: Spectroscopic Observation and Molecular Dynamics Simulation of Ga Surface Segregation in Liquid Pd–Ga Alloys. Issue 70 (14th December 2017) - Grabau, Mathias; Erhard, Jannis; Taccardi, Nicola; Calderon, Sandra Krick; Wasserscheid, Peter; Görling, Andreas; Steinrück, Hans‐Peter; Papp, Christian
Abstract : An inhomogeneous distribution of Palladium atoms in liquid Gallium is shown by means of a combination of angle resolved X‐ray photoelectron spectroscopy and molecular dynamics simulations based on density‐functional theory in a temperature range between room temperature and 750 K. This effect is expected to be of high relevance for a novel liquid metal catalyst consisting of a bimetallic Pd/Ga catalyst supported on porous SiO2 . For more information see the Full Paper by C. Papp et al. onpage 17701 ff.